LATIN LANGUAGE AND HOW TO TEACH WITH MODERN TECHNOLOGY - Matyusupova Shakarjon Bekmamatovna (Journals Park Publishing, 2024)
This article explores the integration of modern technology into the teaching of the Latin language, emphasizing contemporary approaches to engage learners. It covers a range of technological tools, including interactive online platforms, language learning apps, virtual reality tools, and digital textbooks. The annotation highlights the dynamic learning experiences created through these tools, such as gamified elements, adaptive learning systems, and immersive virtual explorations.
Keywords: Interactive Online Platforms, Latin language, Virtual Reality, Podcasts and Online Lectures.